2012
DOI: 10.1371/journal.pone.0042865
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhiza Reduces Adverse Effects of Dark Septate Endophytes (DSE) on Growth of Conifers

Abstract: Mycorrhizal roots are frequently colonized by fungi of the Phialocephala fortinii s.l. – Acephala applanata species complex (PAC). These ascomycetes are common and widespread colonizers of tree roots. Some PAC strains reduce growth increments of their hosts but are beneficial in protecting roots against pathogens. Nothing is known about the effects of PAC on mycorrhizal fungi and the PAC-mycorrhiza association on plant growth, even though these two fungal groups occur closely together in natural habitats. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 58 publications
5
41
1
1
Order By: Relevance
“…This is in contrast to the finding where a positive correlation has been reported between DSE colonization and root length with AM fungal hyphae (Lingfei et al, 2005). Experimental studies on ectomycorrhizal-DSE-plant systems have shown a reduction in DSE fungal colonization in response to ectomycorrhization (Reininger and Sieber, 2012) and this effect was speculated to be the result of competition for space and nutrients or direct antagonism between DSE and mycorrhizal fungi. However, this has yet to be examined for AM and DSE fungal interactions.…”
Section: Dse Fungal Associationcontrasting
confidence: 80%
“…This is in contrast to the finding where a positive correlation has been reported between DSE colonization and root length with AM fungal hyphae (Lingfei et al, 2005). Experimental studies on ectomycorrhizal-DSE-plant systems have shown a reduction in DSE fungal colonization in response to ectomycorrhization (Reininger and Sieber, 2012) and this effect was speculated to be the result of competition for space and nutrients or direct antagonism between DSE and mycorrhizal fungi. However, this has yet to be examined for AM and DSE fungal interactions.…”
Section: Dse Fungal Associationcontrasting
confidence: 80%
“…The dual colonisation of plant roots by DSE and AMF has been recognised since the work of Peyronel (1924). However, reports showing tripartite interactions among DSE, AMF and plants are scarce, with previous authors emphasizing the need for integrating research on mycorrhizal and fungal root endophytes (Scervino et al, 2009;Porras-Alfaro and Bayman, 2011;Reininger and Sieber, 2012). One such study shows that AMF can be influenced by the metabolism of Dreschlera sp., a DSE, with exudates from the latter being found to modulate the mycorrhizal state in the two stages of the life cycle of the symbionts (Scervino et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…DSE have little DOI: 10.14267/phd.2015062 host or habitat specificity; they have been reported in association with ≈600 plants including plants that are non-mycorrhizal, from Antarctic, Arctic, alpine, sub-alpine, and temperate zones, as well as from African coastal plains and lowlands, and from some tropical ecosystems (Jumpponen et al 1998). DSE are often found in boreal and temperate forests associated with the fine roots of trees and shrubs, especially of conifers (Reininger & Sieber, 2012). These fungi are not thought to be pathogenic, as they are observed on healthy fine roots, and in this context, may be referred to as endophytes.…”
Section: Impacts Of Plant-endophyte Interactions On Endophyte Diversitymentioning
confidence: 99%
“…Such a result may imply the ability of this genus to colonize host tissue with no detectable symptom, however these fungi are normally considered as plant DOI: 10.14267/phd.2015062 pathogens. There is a body of evidence that confirms symbiotic life style of Fusarium sp., with plants (Jumpponen et al, 1998); (Kaplan et al, 2013); (Reininger & Sieber, 2012) that altogether they highlight the importance of these fungi in bio-ecosystem and their impact on plant pathophysiology. Some endophytes isolated from cherry rootstocks have formerly been shown to be beneficial to the host.…”
Section: Macrophomina Phaseolina ( Botryosphaeriales) Epicoccum Nigrmentioning
confidence: 99%